ANALISIS BIAYA DIFERENSIAL DALAM PENGAMBILAN KEPUTUSAN MEMBELI ATAU MEMPRODUKSI SENDIRI DAN ANALISIS BIAYA PELUANG PADA RM. PONDOK HIJAU - Elvalina, .; Saerang, David P.E.; Tirayoh, Victorina Z. (ACCOUNTABILITY, 2015)
Economic growth in the era of globalization requires the company to gain maximum profit. Running business requires information. A company should be able to compete with other companies. One of the decisions that must be taken in planning at every alternative is to buy or produce itself a component of raw materials. Differential costs are related to the opportunity costs, which is the differential costs incurred costs as a result of certain decisions while the opportunity costs is the cost incurred when choosing a decision. The purpose of this study to analyze the differential costs in taking the decision to buy or produce itself and to analyze the opportunity cost to decisions taken on RM. Pondok Hijau. The analytical method used is descriptiveÂ  quantitative. Result of differential costs analysis showed that the right decisions can be taken by the management company that manufactures its own because getting a higher differential gain, compared to buying from outside. And of the opportunity costs analysis produce itself rew materials are also more profitable, thus buying from outside becomes more expensive.